(untitled) (Educational Knowledge, 2021)
This article aims to evaluate literacy instruction in basic and secondary education within the public school system of El Salvador during the COVID-19 pandemic. The literature review summarizes initial analyses on the topic and also includes studies that address a crucial issue: teacher training for literacy. The measures adopted and the resources used to ensure the continuity of reading and writing skills development are analyzed, including a review of teacher training, curricula, textbooks, learning guides, and televised lessons. The conclusions highlight the urgent need for adequate teacher training to ensure quality literacy instruction, as well as functional elements and areas for improvement in the educational resources and practices used during this period.